Knowledge, Attitude, and Prevalence of Sexual Violence Among Male Undergraduate Students in a Tertiary Institution in Lagos, Nigeria - Chinazom J Ngini; Kofoworola A Odeyemi; Cassandra C. Nwokoro (American Journal of Men's Health)
Sexual violence robs victims of their autonomy and rights to consent. While myths and gender stereotypes allow the narrative that men cannot be victims thrive, stigma has contributed to the silence and invisibility of male victims of sexual violence. This descriptive, cross-sectional study aimed to assess the knowledge, attitude, and prevalence of male sexual violence among male undergraduates in a tertiary institution in Lagos, Nigeria. A multistage sampling method was used to recruit 400 respondents for this study. Data were collected using interviewer-administered semi-structured questionnaires. The data were analyzed using IBM Statistical Package for Social Sciences Version 26. Chi-Square test was used to test for association between categorical variables and a statistical significance level of 5% ( p  < .05) was set. The mean age of the respondents was 22.7 ± 4.10 years. Most (75%) had good knowledge about sexual violence and 98% had positive attitudes regarding male sexual violence. Thirteen percent, 16%, and 10% of the respondents reported being victims of child sexual abuse, sexual harassment, and sexual assault, respectively. Violence experienced in childhood was found to be a predisposing factor for re-victimization in adulthood ( p value of .000). A multi-sectoral approach to curb sexual violence is recommended.